Cameroon's Infrastructure : A Continental Perspective - Dominguez-Torres, Carolina; Foster, Vivien (World Bank, Washington, DC, 2017)
Better access to improved infrastructure services is an important engine for economic growth. The poor state of infrastructure is a key bottleneck to growth in African countries, and Cameroon is no exception. Between 2000 and 2005, improvements in information and communication technologies boosted Cameroon's growth performance by 1.26 percentage points per capita, while deficient power infrastructure held growth back by 0.28 percentage points. If Cameroon could improve its infrastructure to the level of the middle-income countries of Africa, the growth effect could be on the order of 3.3 percentage points. Cameroon has made significant progress in many aspects of infrastructure. Across a broad range of sectors, the country has made serious efforts to implement institutional reforms with a view to attracting private sector investment. Private sector concessions have been awarded for the Port of Douala, the CAMRAIL railway, the national power utility, and the national water utility (CDE). These arrangements have generally led to performance improvements and attracted significant volumes of finance. Power supply remains expensive and unreliable. Cameroon needs to accelerate the development of some of its prime hydropower sites, which would greatly improve the domestic power situation and potentially allow Cameroon to play its natural role as hydropower exporter to the Central African Power Pool. Cameroon's information and communication technology (ICT) reform remains frozen at an early stage. The telecom incumbent, CAMTEL, remains state-owned and receives substantial public subsidy. The mobile sector is relatively uncompetitive, operating as a duopoly. Moreover, while Cameroon enjoys access to a submarine cable, CAMTEL's monopoly control over the international gateway has prevented consumers from benefiting.